Revolutionizing educational content creation with Canva / Sharifah Sarimah ... [et al.] - Syed Abdullah, Sharifah Sarimah; Ahmad Shukri, Fuziatul Norsyiha; Omar, Mawardi; Samsudin, Norshuhada (Unit Penerbitan JSKM, 2025)
Canva is a dynamic online design tool that has transformed e-learning by making instructional materials more engaging, accessible, and visually appealing. Its intuitive interface, AI-powered features, and real-time collaboration capabilities enable educators and students to create high-quality lesson plans, presentations, and interactive content. Grounded in multimedia and constructivist learning theories, Canva enhances digital literacy, fosters creativity, and supports active learning. Compared to traditional tools like PowerPoint, Canva offers automation, seamless sharing, and extensive multimedia integration. Recent advancements introduce AI-driven design enhancements, further streamlining content creation. Expanding offline access and subject-specific templates could further strengthen Canva’s role in modern education